Cultural Management Strategies in the Merger of Government Organizations: The Experience of 8 Merged Governmental Organizations in Iran - Hosseini shad , Katayoun; Shams , Abdolhamid; Raznahan , Feerooz; Rasouli Ghahroudi , Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This article analyzes the process of merging governmental organizations in Iran with a special focus on managing cultural differences.Methodology: This research uses a case study method to examine government organizations resulting from mergers in the past ten years.Findings: It has shown that the greater the cultural differences between organizations, the more negatively the merger performance is affected in terms of employee job satisfaction and their willingness to remain in the organization.Conclusion: However, if these cultural differences are managed, this relationship can be influenced. Furthermore, this research discusses important practical solutions for managing cultural differences in the merger process, including various aspects such as necessary training to enhance communication skills, increasing tolerance for ambiguity, providing necessary tools for adapting to different cultures, technical training related to organizational structure and functions before the merger, paying attention to the initial conditions of the organization in the merger, the importance of managers' readiness to manage tensions and cultural differences, and more.